2021
DOI: 10.1088/1755-1315/890/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of small islands coral cover and coral-reef fish diversity at Oba Sub-district, Halmahera Island

Abstract: Study on the percentage of coral cover four small islands of Oba Sub-district, Halmahera Island of North Maluku Utara Province was carried out in April 2021.The four small islands of Oba Sub-district studied are Woda Island, Raja Island, Tamin Island, and Guratu Island. The study applied systematic sampling method that included collecting coral reef data using UPT (Underwater Photo Transect) method and coral fish data collection using visual census method. Study results showed that live coral coverage of reefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The present study found that the number of coral reef fish species in China increased with an increase in coral species, with a significant positive correlation. This is similar to Australia [79], Malaysia [10], Indonesia [80], and Tanzania [81]. Komyakova et al [67] reported that the species diversity of fish from Lizard Island had a strong linear relationship with the diversity of coral species, mainly because a large number of fish, especially juveniles, depend on living corals and choose to settle near them.…”
Section: Relationship Between the Species Of Coral And Coral Reef Fishessupporting
confidence: 65%
“…The present study found that the number of coral reef fish species in China increased with an increase in coral species, with a significant positive correlation. This is similar to Australia [79], Malaysia [10], Indonesia [80], and Tanzania [81]. Komyakova et al [67] reported that the species diversity of fish from Lizard Island had a strong linear relationship with the diversity of coral species, mainly because a large number of fish, especially juveniles, depend on living corals and choose to settle near them.…”
Section: Relationship Between the Species Of Coral And Coral Reef Fishessupporting
confidence: 65%
“…Coastal land conversion, terrestrial pollution from trash, household and industrial waste, as well as runoff from maritime transportation, along with coral extraction for construction material, have been identified as anthropogenic factors that have reduced the extent of live coral cover in the waters of Halmahera [4]. Data shows that environmental pressures suspected of being anthropogenic have led to low live coral cover on small islands in the Oba district, Northern Halmahera, which is only around 14.33-39.13% [5]. On a broader scale, out of 12 coral reef stations in the waters of Halmahera, data IOP Publishing doi:10.1088/1755-1315/1328/1/012006 2 reveals that the average extent of dead coral cover in shallow waters (0.5-2.0 m) exceeds that of live coral cover [6].…”
Section: Introductionmentioning
confidence: 99%